(untitled) (Research, Society and Development, 2020)
The genus Capsicum covers the species of peppers and peppers. The production and commercialization of peppers is of great importance in Brazil, however the seeds of this culture tend to present dormancy, a process characterized by delayed germination. Therefore, the objective was to evaluate the effect of different dormancy breaking methods on ’Cumari Verdadeira’ pepper seeds. The experiment was conducted in a completely randomized design with five treatments and five replications. The treatments used were: thermal shock, mechanical scarification, sunlight, chemical scarification (KNO3) and control (seeds without breaking dormancy). The methods of breaking dormancy by thermal shock and mechanical scarification showed the highest germination rates of ’Cumari Verdadeira’ pepper seeds. The Sunlight method showed the worst result in the evaluated conditions, not being recommended for breaking dormancy of ’Cumari Verdadeira’ pepper seeds.